Electrodeposited MoTe2 Thin Films for Photoelectrochemical (PEC) Cell Applications - T. Joseph, Sahaya Anand; Mei Ying, Lim; Mazalan, Nor Hamizah (2011)
Thin films of transition metal chalcogenides, molybdenum ditelluride (MoTe2) have been electrodeposited cathodically on both indium tin oxide-coated conducting glass substrates and stainless steel substrates from H2MoO4 and TeO2 solutions. These MoTe2 thin films are useful as photovoltaic cell and photoelectrochemical (PEC) solar cell. The electrode potential was set to -0.9 V while the bath temperature was maintained at 40±1 ºC with varies deposition time. X-ray diffraction analysis showed the presence of highly textured MoTe2 films with polycrystalline nature. Compositional analysis by EDX gives their stoichiometric relationships. Scanning electron microscope (SEM) was used to study surface morphology and shows that the films are continuous, uniform and useful for device fabrication. The optical absorption spectra showed that the material has an indirect band-gap value of 1.92-2.03 eV with different deposition time. The film also exhibited p-type semiconductor behavior.